The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.21203/rs.3.rs-1234640/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rhizosphere Microbiome of Forest Trees Determines Their Resistance to Soil-borne Pathogens

Abstract: Background and aimsThe ability of plants to cope with environmental pressure and the interaction between rhizosphere microorganisms and host trees play an important role in the stability and function of forest ecosystems. Beneficial microbes recruited to the plant rhizosphere and stably association with tree roots can potentially reduce biotic stress, but the biochemical processes involved in coping with pathogen attack are not fully understood. Here, we aimed to investigate the ecology process of rhizosphere … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…Conversely, due to long-term interactions between trees and the soil microbiome, trees can establish relatively stable rhizosphere microbiome characteristics and plant functional traits [47,69] that support resistance to biotic stresses from soil-borne pathogens. Taken together, optimizing the tree rhizosphere microbiome may be an effective way to improve forest health [70][71][72].…”
Section: Root Microbiome Enhances Plant Disease Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, due to long-term interactions between trees and the soil microbiome, trees can establish relatively stable rhizosphere microbiome characteristics and plant functional traits [47,69] that support resistance to biotic stresses from soil-borne pathogens. Taken together, optimizing the tree rhizosphere microbiome may be an effective way to improve forest health [70][71][72].…”
Section: Root Microbiome Enhances Plant Disease Resistancementioning
confidence: 99%
“…Recently, it was demonstrated that infection of citrus trees by Candidatus Liberibacter asiaticus, associated with Huanglongbing (HLB), was shown to drastically alter the composition of citrus communities across the disease spectrum [126]. Moreover, specific compounds in tree root exudates stimulate key rhizosphere bacteria to cooperate in suppressing soil-borne pathogens [72]. The plant microbiome interacts with pathogens directly or indirectly to strengthen pathogen resistance (Figure 2).…”
Section: The Microbiome Enhances Plant Immunity and Functions As An E...mentioning
confidence: 99%
“…Conversely, due to long-term interactions between trees and the soil microbiome, trees can establish relatively stable rhizosphere microbiome characteristics and plant functional traits [52,74], which enhance biotic stress tolerance against soil-borne pathogens. Taken together, optimizing the tree rhizosphere microbiome may be an effective way to improve forest health [75][76][77].…”
Section: Root Microbiome Enhances Plant Disease Resistancementioning
confidence: 99%
“…Recently, it was demonstrated that the infection of citrus trees by Candidatus Liberibacter asiaticus, associated with HLB, drastically altered the composition of citrus microbiome communities across the disease spectrum [130]. Moreover, specific compounds present in tree root exudates stimulate key rhizosphere bacteria to collaborate in the suppression of soil-borne pathogens [77]. The plant microbiome interacts with pathogens directly or indirectly to strengthen pathogen resistance (Figure 2).…”
Section: The Microbiome Enhances Plant Immunity and Functions As An E...mentioning
confidence: 99%